Boii - Taurisci : Proceedings of the International Seminar, Oberleis-Klement, June 14th-15th 2012. - Karwowski, Maciej; Ramsl, Peter C. (Mitteilungen der Prahistorischen Kommission Ser. ;, 2016)
Annotation